Interindividual Differences in Behavior and Plasticity - Bachtiar, V; Stagg, C (Elsevier, 2013)
Considerable differences exist between individuals both in the way the brain functions normally and how it recovers from injury. Plasticity can be defined as the reorganization of brain connectivity through experience, and animal studies have shown that modulation of intracortical inhibitory circuits is necessary for plasticity induction to occur. There is significant interest among both the clinical and neuroscience communities in investigating the role of inhibitory processes in normal brain function and in how this can help us understand pathophysiology in disease. The ability to measure GABAergic inhibition in vivo using MRS has sparked interest into investigating interindividual differences in the role of GABA in behavior and the effects on GABA concentrations following plasticity-induction paradigms. This chapter will summarize what has been learned about interindividual differences in behavior from MRS studies and explore its potential use in the future.The use of MRS approaches is still in its infancy for applications in neuroscience and many important questions remain to be answered. However, despite these unanswered questions MRS is increasingly being recognized as a robust and powerful tool for the in vivo investigations of neurophysiological changes in humans. © 2014 Elsevier Inc. All rights reserved.